The Teaching Factory Model as a Strategy for Industry Based Learning - Annas Nur Rahmat Hidayat; Azkal Azkiya Ar-Razy; Ammar Alghifari; Andika Bayu Yudistira; Farhan Anam; Hadromi Hadromi; Ahmad Mustamil Khoiron (The Future of Education Journal, 2026)
This study aims to analyze the Teaching Factory (TeFa) model as an industry-oriented learning strategy in vocational education, with particular emphasis on its implementation at SMKN 10 Semarang. A Systematic Literature Review (SLR) approach was employed by examining 20 relevant scholarly articles published between 2021 and 2025. Data were collected through searches in Google Scholar, Garuda, and DOAJ databases and subsequently analyzed using thematic synthesis techniques. The findings indicate that the Teaching Factory (TeFa) model plays a significant role in enhancing students’ technical competencies, problem-solving skills, and work readiness through production-based learning integrated with industry standards. The successful implementation of TeFa is influenced by internal factors, including teachers’ competencies and learning management practices, as well as external factors, such as the availability of facilities and infrastructure and partnerships with industry stakeholders. Implementation strategies include project-based learning, the adoption of authentic production systems, and the strengthening of quality management practices. However, several challenges remain, including limited facilities, disparities in teachers’ competencies, and suboptimal collaboration with industry partners. The study recommends strengthening industry-based training programs, improving educational facilities, and developing strategic partnerships with industry to optimize the implementation of the Teaching Factory model in vocational education.